'More than a travel companion': accompanying partners' experiences of conference attendance. Issue 1 (2nd January 2020) - Yoo, Hyekyung; Wilson, Erica
ABSTRACT: This paper explores the gendered experiences of accompanying women partners in the context of conference travel. While the phenomenon of partners at conferences is not new, their voices remain largely unheard. To explore partners' subjective experiences of conference travel, this study adopts Interpretative Phenomenological Analysis (IPA), drawing from in-depth interviews with 12 accompanying partners. Our findings reveal that accompanying partners generally enjoyed their involvement in, but at the same time felt 'on the margins' of, the conference experience. More specifically, we explore these findings in the specific context of gender and power relations, noting themes such as a sense of liberation, relational intimacy, and feelings of social inclusion and exclusion. There is currently very little literature on the role of accompanying partners in conference attendance, and virtually none viewed from a gendered lens, thus our primary aim is to further critical thought on this nexus.